Seismic Disaster Prevention and Mitigation Research for Long-span Cable-stayed Bridges - Zhang, Liang (International Journal of Natural Resources and Environmental Studies, 2025)
With the rapid advancement of bridge engineering, the construction of long-span cable-stayed bridges has surged, with China now hosting the majority of the world’s largest examples. However, issues such as cable corrosion, aging, and vulnerability to extreme events—including earthquakes—pose significant challenges. Among various natural hazards, earthquakes are particularly destructive, capable of causing widespread structural failure and triggering secondary disasters like landslides and liquefaction. In China, frequent seismic activity has repeatedly damaged vast regions, disrupted transportation networks, and hindered emergency response. As bridges serve as critical components of transportation lifelines, their seismic vulnerability can result in severe economic and humanitarian consequences. Therefore, enhancing the seismic resilience of bridge structures through targeted analysis and design measures is vital to ensuring structural safety and post-disaster accessibility.